9 - History and Literature/Domination and Resistance: Re-Reading the British-Sudan - Afis Ayinde Oladosu (Afrika Zamani, 2022)
This article is hinged on the assumption that the history, and indeed the historiography, of the violent domination of Africa in the late nineteenth and early twentieth century has been written from and therefore could be situated, tentatively, in-between two discordant perspectives: that of the perpetrator and the victim. Whereas it is true that these histories, particularly those of North African States (Egypt and Sudan) have largely been preserved in, and are ac- cessible both in English and Arabic, recent findings have shown that there still exist a third and an un-explored perspective – the experiential-literary-histori- cal. In trying to explore the latter – that in which the Sudanese writer, Muhammad Miftâh al-Faytûrî attempts not only to ‘tell’ but also ‘show’ how and why the themes of domination and resistance in African history should be reread – this study relies on a combination of Western, Eastern and Afro-Ara- bic historical-theoretical styles, including those of al-Jabartî, Ibn Khaldûn, Ali Mazrui, Friedrich Nietzsche and Nawal Saadawi. The article subsequently finds the following questions highly imperative: Exactly how many histories of the domination of and resistance to oppression in Africa are in existence? In other words, what is the difference between Afranj, Africanist and African histories of domination and resistance? What exactly is the philosophy upon which the ‘perpetrator’ premises his ‘history’ of Africa and how is his perspective sub- verted by that of the ‘victim’? How might the attempt to re-read the history of domination and resistance in Africa benefit from the methods and insights of literary writers and critics? How has the literature of the colonial era func- tioned in writing/telling the hi/story behind the hi/story, and in filling the gaps in Africa’s memory and dignity?